206k views
0 votes
-x + 5 + 6x = 1 + 5x + 3

1 Answer

4 votes

Answer:

There are no values of

x

that make the equation true.

No solution

Explanation:

-x + 5 + 6x = 1 + 5x + 3

Group like terms

-x+6x+5=1+5x+3

Add similar elements:-x+6x=5x

5x+5=1+5x+3

Group like terms

5x+5=5x+1+3

Add the numbers 1+3=4

5x+5=5x+4

Subtract 5 from both sides

5x+5-5=5x+4-5

Simplify

5x=5x-1

Subtract 5x from both sides

5x-5x=5x-1-5x

Simplify

0=-1

The sides are not equal

No Solution

User Rmh
by
5.0k points